Causes of perception of insufficient milk supply in Western Australian mothers - Kent, Jacqueline Coral (Matern Child Nutr, 2020)
A perception of insufficient milk supply (PIMS) is associated with early discontinuation of breastfeeding. Ideally, an objective measure of milk supply would either dispel or confirm this perception and provide reassurance or guide professional advice. Clinical signs of sufficient milk intake (steady growth, sufficient elimination, infant alertness and breasts feeling full before breastfeeds and soft after breastfeeds) should provide confidence in milk supply. We surveyed 423 mothers in early lactation who had breastfeeding problems to determine the proportion that had PIMS and to determine if the mothers with PIMS relied on these clinical signs or other perceptions of their infants' behaviour as indications of insufficient milk supply. By 3 weeks after birth, we found that the rate of PIMS among mothers with breastfeeding problems was 44%. Supplementary infant formula was being given to 66% of the infants, so the clinical indications were that milk intake was sufficient, but 74% of the mothers with PIMS cited concerns that their infants did not appear satisfied after breastfeeds. After targeted advice from lactation consultants, mothers with PIMS showed positive changes in their perceptions of their milk supply, underlining the value of professional guidance soon after birth. We conclude that an appearance of infant dissatisfaction is the major cause of PIMS in Western Australia.